FEASIBILITY ANALYSIS OF SHRIMP PASTE PROCESSING BUSINESS IN TANJUNG PASIR VILLAGE, TANAH MERAH SUB-DISTRICT, INDRAGIRI HILIR REGENCY, RIAU PROVINCE - Afandy, Muhammad; Arief, Hazmi; Hendrik, Hendrik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The fishery product processing industry has become an important economic sector, especially in maritime countries like Indonesia. One processing business with great potential in Indonesia is rebon shrimp paste. The shrimp paste processing business has developed in Tanjung Pasir Village. The processor can produce shrimp paste with ±1,500kg/month of raw materials. This study aims to calculate the total investment, revenue, and profit and analyze the feasibility of the shrimp paste processing business in Tanjung Pasir Village. The survey method was used, and interviews were conducted with ten shrimp paste processing business owners. Data analysis used is an investment, revenue, profit, and business feasibility with Revenue Cost Ratio (RCR), Payback Period of Capital (PPC), and Financial Rate of Return (FRR) criteria. The results showed that the total investment of the shrimp paste processing business using a 6-bag corrugated net amounted to IDR 62,161,000, 3 bags to IDR 51,452,300, and two bags to IDR 48,028,750. Using a 6-bag corrugated net, gross revenue per year amounted to IDR 133,605,000, three bags to IDR 96,063,600, and 2 bags to IDR 72,206,250. Profit per year using a 6-bag corrugated net is IDR60,735,500, 3-bag is IDR 39,751,650, and 2-bag is IDR25,669,250. The RCR value of a shrimp paste processing business using a 6-bag corrugated net is 1.8, 3-bag is 1.7, and 2-bag is 1.6. PPC value for the 6-bag corrugated net for 1 year, 3-bag for 1 year, 4 months, and 2-bag for 1 year, 11 months. The FRR value for 6-bag corrugated net is 97.71%, 3-bag 77.26% and 2-bag 53.45%.